Alpha-Fetoprotein and Novel Tumor Biomarkers as Predictors of Hepatocellular Carcinoma Recurrence after Surgery: A Brilliant Star Raises Again - Quirino Lai; Fabio Melandro; Rafael S. Pinheiro; Andrea Donfrancesco; Bashir A. Fadel; Giovanni B. Levi Sandri; Massimo Rossi; Pasquale B. Berloco; Fabrizio M. Frattaroli (International Journal of Hepatology)
Alpha-fetoprotein (AFP), des-γ-carboxy prothrombin (DCP), and lens culinaris agglutinin-reactive fraction of AFP (AFP-L3) have been developed with the intent to detect hepatocellular carcinoma (HCC) and for the surveillance of at-risk patients. However, at present, none of these tests can be recommended to survey cirrhotic patients at risk for HCC development because of their suboptimal ability for routine clinical practice in HCC diagnosis. Starting from these considerations, these markers have been therefore routinely and successfully used as predictors of survival and HCC recurrence in patients treated with curative intent. All these markers have been largely used as predictors in patients treated with hepatic resection or locoregional therapies, mainly in Eastern countries. In recent studies, AFP has been proposed as predictor of recurrence after liver transplantation and as selector of patients in the waiting list. Use of AFP modification during the waiting list for LT is still under investigation, potentially representing a very interesting tool for patient selection. The development of a new predictive model combining radiological and biological features based on biological markers is strongly required. New genetic markers are continuously discovered, but they are not already fully available in the clinical practice.